PENERAPAN STRATEGI PEMBELAJARAN AKTIF ROLLED UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA IPA FISIKA KELAS VII SMPN 40 PEKANBARU - Firharianti Safitri; Azizahwati '; Muhammad Sahal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstrack: This research aimed to describe and find out the improvement of the students’ motivation learning achievement by using learning active strategy of Rolled. Type of this research is a quasi-experimental, with nonequivalent control group design. The subject of this research is students class VII at SMPN 40 Pekanbaru, total of 176 students as divide into two class, experimental class and control class. The data in this research is a score of motivation before and after learning physics by implementation of learning active strategy of rolled model with descriptive and inferential analysis.Then, measured the improvement of the students’ motivation by normalized gain (gain-N) and t-test. The descriptive analysis score motivation of students at experimental class in middle category and increase in the middle category with N-Gain 0.49, and the control class in the middle category with N-Gain 0,37. This proved by inferential analysis, the analyzed shows t(44) = 7.409 means p < 0.05, then Ho is rejected. Which means that there are difference in motivation of learning between experiment class and control class. It can therefore be concluded that the implementation of learning active strategy of rolled to students’ motivation learning achievement in physics on science at the seven grade of junior high school 40 pekanbar.